The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.biopsycho.2019.107809
|View full text |Cite
|
Sign up to set email alerts
|

Biological embedding of maternal postpartum depressive symptoms: The potential role of cortisol and telomere length

Abstract: Although maternal postpartum depressive symptoms (PDS) are associated with child behavior problems, the underlying biological mechanisms are poorly understood. Thus, the current study focused on 193 healthy mother-child dyads and investigated child cortisol and telomere length as potential mediating factors. At 3 and 6 months postpartum, mothers reported on PDS. At age 6, children provided saliva and buccal swab samples. At age 10, mothers and children reported on child behavior problems. Structural equation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…Alternatively, because the mother-reported association between transient fluctuations in maternal depression symptomatology at 12.5 years and children’s internalizing problems were not found in the child-reported measurement, it is possible that the current symptomatology of the mother affected her view of the child’s behavior, leading to biased reporting of children’s problems (Beijers et al, 2020; Fergusson et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, because the mother-reported association between transient fluctuations in maternal depression symptomatology at 12.5 years and children’s internalizing problems were not found in the child-reported measurement, it is possible that the current symptomatology of the mother affected her view of the child’s behavior, leading to biased reporting of children’s problems (Beijers et al, 2020; Fergusson et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…This gave us the opportunity to compare mothers and children’s views on the child’s developmental problems. The significant difference between mother and child reports of internalizing and externalizing problems underlines the importance of including the child’s own observation next to the maternal report (Beijers et al, 2020; De Los Reyes & Kazdin, 2005). However, in our study, we found a much higher correlation between mother- and child-reported internalizing problems compared to externalizing problems.…”
Section: Discussionmentioning
confidence: 99%
“…The general rule of thumb is that a Cronbach’s alpha of 0.70 and above is good, but the Cronbach’s alpha of the child-reported Internalizing Problems subscale is questionable. However, as the Cronbach’s alpha is close to 0.70, and previous research has indicated the value of child report above and beyond the maternal report and, especially in case of internalizing problems [ 21 ], we continued analyzing all subscales.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between psychological symptoms and telomere shortening is expected. Shorter telomeres were observed in mothers with postpartum depression, and it was as a predictive feature of the presence of internalizing and externalizing symptoms in children, suggesting the stressful features lived by mothers are underlying the behavioral problems in children [30]. The findings on externalizing and internalizing symptoms deserve a careful evaluation of the stress response and subsequent biological changes, in both conditions, to have a clear picture concerning their impacts.…”
Section: Discussionmentioning
confidence: 99%